Emerging Role of Palliative Care in Patients with Advanced Liver Disease - Jordan, Roberta I.; Tandon, Puneeta (Seminars in Liver Disease, 2020)
Advanced liver disease is increasing in mortality and morbidity worldwide, as a result of growing alcohol consumption, obesity, and viral hepatitis infection. Alongside efforts to reduce these factors, it is clear that we must identify the considerable palliative care needs of these patients in order to improve quality of life and reduce symptom burden. Our review focuses on the current state of palliative and end-of-life care for patients with advanced liver disease, the significant associated symptom burden in this disease group, identified level of involvement and potential benefits of specialist palliative care, as well as possible barriers to accessing this care. We demonstrate that although palliative care involvement varies considerably worldwide, there is much opportunity for improvement. Further research is needed to determine new interventions and models of care that may improve access for patients with liver disease, including an expansion of providers comfortable with generalist palliative care.
Keywords: palliative; end-of-life care; hepatology; symptom burden